Shotgun proteomics study of early biofilm formation process of Acidithiobacillus ferrooxidans ATCC 23270 on pyrite. Issue 7 (4th March 2013) - Vera, Mario; Krok, Beate; Bellenberg, Sören; Sand, Wolfgang; Poetsch, Ansgar
Abstract : Acidithiobacillus ferrooxidans is a chemolithoautotrophic, mesophilic Gram‐negative bacterium able to oxidize ferrous iron, sulfur, and metal sulfides. It forms monolayer biofilms where extracellular polymeric substances are essential for cell attachment and metal sulfide leaching. High‐throughput proteomics has been applied to study the early process of biofilm formation on pyrite by At. ferrooxidans ATCC 23270. After 24 h contact with the mineral, planktonic and sessile (biofilm) cell subpopulations were separated and proteins extracted. In total, 1319 proteins were detected in both samples. Sixty‐two of these were found to be increased in biofilms. Additionally, 25 proteins were found to be decreased in the biofilm cell subpopulation. Three transcriptional factors were found to be increased or decreased among both cell subpopulations, suggesting their potential involvement in the regulation of these processes. Although no significant differences were observed for the known proteins related to ferrous iron and sulfur oxidation pathways among both cell subpopulations, the results presented here show that the early steps of At. ferrooxidans biofilm formation consist of a set of metabolic adaptations following cell attachment to the mineral surface. Functions such as extracellular polymeric substances biosynthesis seem to be pivotal. This first high‐throughput proteomic study may also contribute to the annotation of several unknown At. ferrooxidans proteins found.